The stone idol - Dixon, Franklin W. (New York : Grosset & Dunlap, 2005)
Their search for an Easter Island idol takes the Hardy boys to Easter Island and on to investigate the theft of government material in Antarctica.
Keywords: Mystery and detective stories; Easter Island -- Juvenile fiction; Antarctica -- Juvenile fiction